PENGARUH AUDIOVISUAL MENONTON FILM KARTUN TERHADAP TINGKAT KECEMASAN SAAT PROSEDUR INJEKSI PADA ANAK PRASEKOLAH - Fatmawati, Lilis; Syaiful, Yuanita; Ratnawati, Diyah (Universitas Nahdlatul Ulama Surabaya, 2019)
Abstract :Among preschoolers,  illness is  a scary thing. Children have limitations in coping mechanisms to overcome the crisis. Audiovisual intervention in watching cartoons is a distraction technique to reduce anxiety in children. The purpose of the study was to analyze the effect of audiovisual cartoon movie on anxiety levels during injection procedures in preschool children. The design of this study was using Pre-experimental pretest and posttest one group design. The research collecting the data using purposive sampling technique on 28 respondents. Independent variable audiovisual watching cartoons, while dependent variable is anxiety level. The instrument used is SOP and HAR-S anxiety scale. Statistical tests using the Paired Sample T-Test, with significance p <0.05. From the results of the statistical analysis, the sig value was obtained (p = 0.001, t=11.71) which means an audiovisual intervention by on watching  cartoons movie was effective to reduce  anxiety levels during the injection procedure in preschool children. We suggest that audiovisual intervention by watching cartoons movie  can be applied as one of the nursing interventions to reduce anxiety during injection procedures in preschool children.   Keywords: Anxiety, Audiovisual, Injection Procedure, Preschool Children